Quality of Life in Deafblind People and Its Effect on the Processes of Educational Adaptation and Social Inclusion in Canary Islands, Spain - María del Carmen Rodríguez-Jiménez; David Pérez-Jorge; Irene Puerta-Araña; Eva Ariño-Mateo (MDPI AG, 2022)
Deafblindness is a unique and complex disability. Research on the needs and quality of life are scarce; as well as the lack of adequate knowledge, training and lack of qualified professionals to serve this group. All this justifies the sense and interest of this study. This study is derived from the project with reference 2020EDU04. Design: The study is descriptive, cross-sectional and quantitative-qualitative research design was conducted. Objectives: Know and analyze the needs of adult deafblind people in order to contribute to improving their quality of life. Method: Sample of 16 adults with double sensory loss (hearing and vision) residing in the Autonomous Community of the Canary Islands (Spain) was used. Instruments: The FUMAT Scale was used to measure personal development; self-determination; interpersonal relationships; social inclusion; rights of deafblind people; emotional well-being; physical well-being and material well-being. In addition, a semi-structured interview is conducted. Results by dimensions: Personal development: The professionals did not have specialized training to provide an educational response. Physical well-being: 68% of the sample had other health problems associated with deafblindness. Interpersonal relationships: 100% of the sample reported communication problems in the family environment. Social inclusion: They reported difficulties in accessing educational and leisure activities. Material well-being: In general, they stated that they have the material resources necessary for their daily lives. Self-determination: they consider that they have decision-making capacity in basic aspects of daily life. Rights: Deafblind people state that they have limitations in exercising their rights. Based on the interviews, it was observed that the people with the greatest difficulties in daily life are those who presented the greatest visual commitment. Conclusion: The etiology does not determine the quality of life of deafblind people, but communication conditions interpersonal relationships and personal development, and therefore their quality of life.